Looking like a proper baby: nurses' experiences of caring for extremely premature infants. Issue 1 (9th May 2014) - Green, Janet; Darbyshire, Philip; Adams, Anne; Jackson, Debra
<x xml:space="preserve">Abstract</x> Aims and objectives To explore the ways in which neonatal nurses draw meaning and deal with the challenges associated with caring for extremely premature babies. Background Current literature suggests that nurses face challenges providing care to certain patients because of their appearance. This article will focus on those difficulties in relation to neonatal nurses caring for infants ≤24 weeks of gestation in the neonatal intensive care unit. Extremely premature babies often have more the appearance of a foetus than the appearance of a baby, and this presented challenges for the neonatal nurses. Design This paper has used interviews and drew insights from interpretative phenomenology. Methods This paper used a series of interviews in a qualitative study informed by phenomenology. The analysis of the interview data involved the discovery of thematic statements and the analysis of the emerging themes. Results This paper outlines the difficulties experienced by neonatal nurses when caring for a baby that resembles a foetus more than it does a full‐term infant. The theme the challenges of caregiving was captured by three subthemes: A foetus or a viable baby?; protective strategies and attributing personality. Conclusion This study identified that neonatal nurses experience a range of difficulties when providing care for an infant who resembled a foetus rather than a full‐term baby. They employed strategies that minimised the foetal appearance and maximised the appearance and attributes associated with a newborn baby. Relevance to clinical practice Increasing survival of extremely premature infants will see nurses caring for more babies ≤24 weeks of gestation. Caring for extremely premature babies has been reported as being stressful. It is important to understand the nature of stress facing this highly specialised neonatal nursing workforce. Supportive work environments could help to ameliorate stress, facilitate better care of tiny babies and decrease staff turnover.